EFFECTIVITY OF LIGHT INTENSITY ON COLOR GRADATION AND CAROTENOIDS CONTENT OF Lobophyllia hemprichii - Ahmad Mustawa; Esti Harpeni; Moh. Muhaemin (Jurusan Perikanan dan Kelautan, 2017)
L. hemprichii is one of the marine ecosystems with high biodiversity and the most productive. The more healthy corals, the higher productivity in the sea. The existence of light is needed for L. hemprichii for its growth. Moreover L. hemprichii has color that produced by symbiotic algae pigments such as carotenoid pigments. Carotenoid pigment has active role to absorb light in process of photosynthetic of algae symbionts. The aims of this study were to gain different effects of light intensity to color gradation of red and carotenoids content of L. hemprichii. The study was conducted by placing L. hemprichii into aquriums with ICR treatment (Low Light Intensity = 1514 Lux), ICS treatment (Medium Light Intensity = 3028 Lux), treatment ICR (High Light Intensity = 4547 Lux). The results showed that the light intensity affect the color gradation of coral L. hemprichii and light intensity affect the concentration of total carotenoid pigment L. hempirchii. The best light intensity for L. hempirchii color and carotenoid pigment production was high light intensity (4547 Lux).